MPEG digital compression and analogue videotape a comparison of moving images and electroencephalogram data in epileptic patients. - Akazawa, Kouhei
The objective of this study was to compare the clinical usefulness, in the field of epileptology, of digital moving images and electroencephalogram (EEG) waveforms by Motion Pcitures Expert Group compression algorithms (MPEG-1 and MPEG-2) to that of conventional analogue recording. Three epileptic seizure scenes consisting of moving images and the corresponding EEG waveforms in an epileptic patient were selected as the images to be evaluated. Each scene was recorded using MPEG-1, MPEG-2 and videotape. Ten doctors used six criteria to evaluate the quality of moving images, EEG data and audio. Analysis of variance and Bonferroni tests indicated that the image quality of MPEG-2 was superior to that of MPEG-1 or videotape for all criteria. Furthermore, MPEG-2 obtained much higher scores in EEG waveform quality than did the other modalities. Our findings suggested that data from MPEG-2 images will lead to more precise diagnosis and treatment decision-making than data from analogue videotape recordings
Keywords: Comparative study; Epilepsy; Moving image; MPEG; Telecommunication